2x+5y-3=5

来源:学生作业帮助网 编辑:作业帮 时间:2017/12/18 16:53:29
已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)

已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)已知x-y/x+y=3,求代数式5(x-y)/x+y-x+y/2(x-y)已知x-y/x+y=3,求代数式5(x-y)/x+y

x+y/2+x-y/6=5 2(x+y)-3(x-y)=-2

x+y/2+x-y/6=52(x+y)-3(x-y)=-2x+y/2+x-y/6=52(x+y)-3(x-y)=-2x+y/2+x-y/6=52(x+y)-3(x-y)=-2由式(1)获得3X+3γ-

3(x+y)+2(x-y)=36 4(x+y)-5(x-y)=2

3(x+y)+2(x-y)=364(x+y)-5(x-y)=23(x+y)+2(x-y)=364(x+y)-5(x-y)=23(x+y)+2(x-y)=364(x+y)-5(x-y)=23(x+y)+

(x-y)/(x+y)=3求( 3x-2y-1)/(x+y-5)

(x-y)/(x+y)=3求(3x-2y-1)/(x+y-5)(x-y)/(x+y)=3求(3x-2y-1)/(x+y-5)(x-y)/(x+y)=3求(3x-2y-1)/(x+y-5)(x-y)/(

4(x-y)-3(x-y)=9 5(x-y)+2(x-y)=11

4(x-y)-3(x-y)=95(x-y)+2(x-y)=114(x-y)-3(x-y)=95(x-y)+2(x-y)=114(x-y)-3(x-y)=95(x-y)+2(x-y)=11打错了吧,这样

3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27

3(x+y)-4(x-y)=11,2(x-y)+5(x+y)=273(x+y)-4(x-y)=11,2(x-y)+5(x+y)=273(x+y)-4(x-y)=11,2(x-y)+5(x+y)=27化

6(x-y)-2(x+y)=14 3(x-y)+(x+y)=5

6(x-y)-2(x+y)=143(x-y)+(x+y)=56(x-y)-2(x+y)=143(x-y)+(x+y)=56(x-y)-2(x+y)=143(x-y)+(x+y)=5设x-y=mx+y=

先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y) x=4 y=5

先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y)x=4y=5先化简再求值(x-y)(x-2y)+(x-2y)(x-3y)-2(x-3y)(x-4y)x=4y=5

{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?

{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?{(x+y)/2+(x-y)/3=1,(x+y)-5(x-y)=2.求x=?,y=?{(x+y)/2+(x-y)/3

化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1

化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,其中x=-1,y=1化简[(3x+4y)^2-(2x+y)(2x-y)+(-x+y)(5x-y)]除以-2y,

(x+y-5)*(x+y-5)+(x-y+3)=0 x*x-y*y

(x+y-5)*(x+y-5)+(x-y+3)=0x*x-y*y(x+y-5)*(x+y-5)+(x-y+3)=0x*x-y*y(x+y-5)*(x+y-5)+(x-y+3)=0x*x-y*y这是什么

已知:3x-5y=0,求x/y,x-y/y,x-y/x

已知:3x-5y=0,求x/y,x-y/y,x-y/x已知:3x-5y=0,求x/y,x-y/y,x-y/x已知:3x-5y=0,求x/y,x-y/y,x-y/x3x-5y=03x=5y→x/y=5/

(4x-2y-z)-{5x[8y-2y-(x+y)]-x+(3y-10z)]=? kuaihuajian

(4x-2y-z)-{5x[8y-2y-(x+y)]-x+(3y-10z)]=?kuaihuajian(4x-2y-z)-{5x[8y-2y-(x+y)]-x+(3y-10z)]=?kuaihuaji

先化简,再求值 [2/3x - 2/x+y(x+y/3x -x-y)]*x/x-y,其中5x+3y=0

先化简,再求值[2/3x-2/x+y(x+y/3x-x-y)]*x/x-y,其中5x+3y=0先化简,再求值[2/3x-2/x+y(x+y/3x-x-y)]*x/x-y,其中5x+3y=0先化简,再求

先化简,再求值:[3x-2/x+y(x+y/3x-x-y)]/(x-y/x),其中5x+3y=0

先化简,再求值:[3x-2/x+y(x+y/3x-x-y)]/(x-y/x),其中5x+3y=0先化简,再求值:[3x-2/x+y(x+y/3x-x-y)]/(x-y/x),其中5x+3y=0先化简,

化简:5(x-y)+2(x+y)-3(x-y)

化简:5(x-y)+2(x+y)-3(x-y)化简:5(x-y)+2(x+y)-3(x-y)化简:5(x-y)+2(x+y)-3(x-y)5(x-y)+2(x+y)-3(x-y)=5x-5y+2x+2

5x=3y,(2x+y)的平方=5x(x+y)+9

5x=3y,(2x+y)的平方=5x(x+y)+95x=3y,(2x+y)的平方=5x(x+y)+95x=3y,(2x+y)的平方=5x(x+y)+95x=3y,x=3y/5(2x+y)的平方=5x(

3X=5Y (X+Y)*3X=(2Y+X)*4+2*2

3X=5Y(X+Y)*3X=(2Y+X)*4+2*23X=5Y(X+Y)*3X=(2Y+X)*4+2*23X=5Y(X+Y)*3X=(2Y+X)*4+2*23X=5YX:Y=5:3设X=5ky=3k则

3x+5y-(x+y)=6 2(x+y)-3x=-7

3x+5y-(x+y)=62(x+y)-3x=-73x+5y-(x+y)=62(x+y)-3x=-73x+5y-(x+y)=62(x+y)-3x=-7由题,x+2y=3,2y-x=-7,两式相加得4y

5X+Y=3 X+5Y=2 求x和y.5X+Y=3X+5Y=2求x和y.

5X+Y=3X+5Y=2求x和y.5X+Y=3X+5Y=2求x和y.5X+Y=3X+5Y=2求x和y.5X+Y=3X+5Y=2求x和y.5X+Y=3X+5Y=2求x和y.5X+Y=3X+5Y=2求x和